Patently Controversial: Markets, Morals, and the President's Proposal for Embryonic Stem Cell Research - Fins, Joseph (Kennedy Institute of Ethics journal, 2002)
, This essay considers the implications of President George W. Bush's proposal for human embryonic stem cell research. Through the perspective of patent law, privacy, and informed consent, we elucidate the ongoing controversy about the moral standing of human embryonic stem cells and their derivatives and consider how the inconsistencies in the president's proposal will affect clinical practice and research.